Analisis Keuntungan dan Kendala Penerapan Konsep Sistem Pertanian Terpadu (SPT) di Indonesia - Hidayati, Filya; Yonariza, Yonariza; Nofialdi, Nofialdi; Yuzaria, Dwi (Department of Agribusiness, Halu Oleo University, 2020)
This research is to find the development of integrated agricultural systems implemented in several countries and in Indonesia and the constraints that occur in the implementation of integrated farming systems (IFS). IFS is a solution to a crisis situation where agriculture or livestock can no longer support all the economic, ecological, ecosystem, social, and technological aspects. This integrated farming system combines agriculture with livestock, fisheries, forestry, and tourism. Plants with livestock are interconnected and mutually beneficial and mutually supportive. This incorporation involves utilizing all existing resources in its entirety, to produce by-products in the form of waste utilization from agriculture and livestock (zero waste) and supported by technological developments to support it. The method uses integrated farming systems by looking for similarities, differences, views, and summarizes the results of previous research. This research covers literature studies on the development, implementation, and constraints that occur in integrated farming systems in several countries in the world, and Indonesia with various models of integrated farming systems are applied. Based on a literature study found that integrated farming systems can improve food security, farmer welfare, increase soil fertility, increase employment, create renewable technology, and the importance of government support to create opportunities for farmers in increasing their agricultural scale and more prosperous farmers in the future. In addition, there are also obstacles in IFS such as the absence of a correct understanding (farmers and facilitators), yield and productivity levels have not convinced farmers, the model is not in accordance with the ecosystem, has not utilized local potential, the existence of integrators have not been considered, yet the existence of comprehensive studies and agricultural development policies are not pro-farmers and lack of supporting technology.